STUDY OF TECHNOLOGICAL PROPERTIES OF SUBSTANCE AND BASIC COMPOSITION FOR OBTAINING THE DRUG PRODUCT OF "BIOMAYRIN" - N. E. Mamatmusaeva; Sh. A. Shomuratov; B. Т. Sagdullaev; A. S. Turaev (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2018)
The low-molecular synthetic drugs, used for the treatment of tuberculosis nowadays, are highly toxic and do not have the ability to selectively penetrate into phagocytes; besides, they are quickly removed from the body without providing a prolonged action. To solve the existing problem, modern methods of modifying the properties of biologically active compounds by joint synthesis of antibiotic with high-molecular compounds, by incorporating antituberculosis drugs into the carrier polymers have been applied. These methods have made it possible to purposefully change their physical-chemical and medical-biological properties.The aim of the work is to evaluate the technological properties of the substance of the combined anti-tuberculosis drug "Biomayrin" and to work out its drug product.Materials and methods. The object of the study was the substance of the original medicinal preparation "Biomayrin", obtained on the basis of high molecular compounds, and synthetic antituberculosis drugs by the molecular design method.Results and discussion. The results of the comparative analysis of technological properties of the biomayrin substance and the prepared capsular masses with the addition of various antifriction agents are shown in the article. The introduction of antifriction agents greatly improved the technological properties of the substance. As a result, the angle of the natural slope decreased from 42.7° to 31-39°, and the fl owability increased to 2.6-3.6 g/s.Conclusion. Thus, the infl uence of various antifriction agents on the technological properties of the substance of the anti-tuberculosis drug "Biomayrin" was investigated, which allowed to work out the optimal composition of the drug product.